Ho Chi Minh Communist Youth Union’s Role in Educating National Culture among University Students - Van Vu Hong (Besari: Journal of Social and Cultural Studies, 2025)
This study aims to explore the strategic role of the Vietnam’s Ho Chi Minh Communist Youth Union within the university environment in educating the younger generation about national culture. In addition to highlighting its positive contributions, this study also critically identifies various obstacles and root causes that limit the organization's effectiveness in the process of internalizing cultural values. Through a theoretical approach and supported by the results of a survey of 167 respondents from among lecturers and students, it was found that the presence of this organization is crucial in shaping the character of students. These findings are expected to provide scientific and practical contributions for socio-political organizations and universities in formulating strategic solutions to optimize the role of student unions in the present and future. With the right orientation, it is hoped that a new generation of Vietnamese will emerge who are not only professionally skilled in their fields but also possess integrity and a strong pride in the nation's cultural heritage and noble values. Penelitian ini bertujuan untuk mendalami peran strategis Persatuan Pemuda Komunis Ho Chi Minh Vietnam di lingkungan universitas dalam mengedukasi budaya nasional kepada generasi muda. Selain menyoroti kontribusi positifnya, studi ini juga secara kritis mengidentifikasi berbagai hambatan serta akar permasalahan yang membatasi efektivitas organisasi tersebut dalam proses internalisasi nilai-nilai budaya. Melalui pendekatan teoretis dan diperkuat oleh hasil survei terhadap 167 responden dari kalangan dosen serta mahasiswa, ditemukan bahwa kehadiran organisasi ini sangat krusial dalam membentuk karakter mahasiswa. Temuan ini diharapkan mampu memberikan kontribusi ilmiah dan praktis bagi organisasi sosial-politik maupun perguruan tinggi untuk merumuskan solusi strategis guna mengoptimalkan peran serikat mahasiswa. Dengan orientasi yang tepat, diharapkan lahir generasi baru Vietnam yang tidak hanya mahir secara profesional di bidangnya, tetapi juga memiliki integritas serta kebanggaan yang kuat terhadap warisan dan nilai-nilai luhur budaya bangsa.